"The Good Old R01": Challenging Downward Funding Success Trends at the National Heart, Lung, and Blood Institute. Issue 10 (13th May 2016) - Oh, Young S.; Robinson, Valerie; Stanley, Dennis V.; Tolunay, Eser; Kim, Dong-Yun; Galis, Zorina S.
Abstract : Supplemental Digital Content is available in the text.